2016
DOI: 10.1158/0008-5472.can-15-3432
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from High-Grade Glioma Exchange Diverse Pro-oncogenic Signals That Maintain Intratumoral Heterogeneity

Abstract: A lack of experimental models of tumor heterogeneity limits our knowledge of the complex subpopulation dynamics within the tumor ecosystem. In high grade gliomas (HGG), distinct hierarchical cell populations arise from different glioma stem-like cell (GSC) subpopulations. Extracellular vesicles (EV) shed by cells may serve as conduits of genetic and signaling communications, however, little is known about how HGG heterogeneity may impact EV content and activity. In this study, we performed a proteomic analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 20 publications
5
111
0
Order By: Relevance
“…A recent report demonstrated that GSC-derived extracellular vesicles support intratumoral heterogeneity and that GSCs of the mesenchymal subtype had an increased proliferative effect on proneural subtype GSCs whereas treatment with self-exosomes had no effect [28]. Consistent with this report, we observed minimal effects on GSC growth when treated with self-derived exosomes.…”
Section: Discussionsupporting
confidence: 91%
“…A recent report demonstrated that GSC-derived extracellular vesicles support intratumoral heterogeneity and that GSCs of the mesenchymal subtype had an increased proliferative effect on proneural subtype GSCs whereas treatment with self-exosomes had no effect [28]. Consistent with this report, we observed minimal effects on GSC growth when treated with self-derived exosomes.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the generality of EV properties across larger panels of GBM and GSC isolates or subtypes, and their representation in intact tissues are still to be addressed more fully, and are currently under study. Moreover, therapy-induced evolution of GSCs [55] is likely to impact EV profiles, as we recently documented [56], while intra-tumoural interactions of different GSC population may also involve EV-dependent signals [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Suppression of immune cells (dendritic, NK-, and T-cells) through exosome communication plays an important role in tumor progression [217]. In the lung, immunosuppression by alveolar macrophages is a normal physiological, homeostatic function, and it must be to handle the constant onslaught of antigens through breathing [295]. Homeostatic balance between immunosuppression and immunoresponsiveness in the lung becomes dysregulated in tumor progression [148,163].…”
Section: Pan-cancer Analysismentioning
confidence: 99%